2022
DOI: 10.1186/s12890-022-02138-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with comorbid asthma in patients with chronic rhinosinusitis with nasal polyps: a cross-sectional study

Abstract: Background Although 20–60% of patients with chronic rhinosinusitis with nasal polyps (CRSwNP) have asthma, the risk factors associated with comorbid asthma are not clear. The aim of the study was to investigate the factors associated with asthma, and develop a practical scoring system to screen asthma comorbidity in CRSwNP patients. Methods This report describes a cross-sectional study with consecutive CRSwNP patients. Two cohorts of CRSwNP patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…The ndings of the study have additionally shown that except for underdiagnosed, asthma in patients with CRSwNP is more severe than those without CRSwNP, emphasizing that it is important to early identify, monitor and treat comorbid asthma in CRSwNP patients. Although we have previously demonstrated that a scoring system based on female gender, history of AR, increased blood EOS, and IgE levels (FAIE) is useful for screening comorbid asthma in patients with CRSwNP, [4] the current ndings suggest that a decreased FEF 50 may be superior to the FAIE system in this respect. As decreased perception of asthma symptoms and BD reversibility test, which is prone to be negative, are the main indicators of underdiagnosis of comorbid asthma in CRSwNP patients, [4] we suggest that determination of variable air ow limitation in patients with CRSwNP is probably better based on an improvement of FEV 1 after anti-in ammatory treatment, especially in suspected asthmatics with FEF 50 %pred <60% and poor response to short-acting beta 2-agonists.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…The ndings of the study have additionally shown that except for underdiagnosed, asthma in patients with CRSwNP is more severe than those without CRSwNP, emphasizing that it is important to early identify, monitor and treat comorbid asthma in CRSwNP patients. Although we have previously demonstrated that a scoring system based on female gender, history of AR, increased blood EOS, and IgE levels (FAIE) is useful for screening comorbid asthma in patients with CRSwNP, [4] the current ndings suggest that a decreased FEF 50 may be superior to the FAIE system in this respect. As decreased perception of asthma symptoms and BD reversibility test, which is prone to be negative, are the main indicators of underdiagnosis of comorbid asthma in CRSwNP patients, [4] we suggest that determination of variable air ow limitation in patients with CRSwNP is probably better based on an improvement of FEV 1 after anti-in ammatory treatment, especially in suspected asthmatics with FEF 50 %pred <60% and poor response to short-acting beta 2-agonists.…”
mentioning
confidence: 64%
“…Although we have previously demonstrated that a scoring system based on female gender, history of AR, increased blood EOS, and IgE levels (FAIE) is useful for screening comorbid asthma in patients with CRSwNP, [4] the current ndings suggest that a decreased FEF 50 may be superior to the FAIE system in this respect. As decreased perception of asthma symptoms and BD reversibility test, which is prone to be negative, are the main indicators of underdiagnosis of comorbid asthma in CRSwNP patients, [4] we suggest that determination of variable air ow limitation in patients with CRSwNP is probably better based on an improvement of FEV 1 after anti-in ammatory treatment, especially in suspected asthmatics with FEF 50 %pred <60% and poor response to short-acting beta 2-agonists. Decreased FEF 50 as an indicator of PAL also suggests that monitoring FEF 50 should be helpful for the assessment of asthma control and medication adjustment in asthmatics with comorbid CRSwNP.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Os desfechos do estudo mostraram o sexo feminino e a rinite alérgica como fator etiológico independete pra asma. A rinite alérgica pode ser determinada por características clínicas típicas como rinorreia, espirros, obstrução e prurido e sensibilidade a pelo menos um aeroalérgeno comum ácaros e pólen, por exemplo (Li et al, 2022). Os níveis séricos de IgE total e a contagem de eosinófilos no sangue também foram associados ao risco para a asma em pacientes com RSCcPN.…”
Section: Principais Achados Conclusõesunclassified
“…Therefore, the aim of this study was to describe the pattern profile of monosensitization and polysensitization for common allergens in 938 IgE-positive children. Increasing evidence suggests that elevated levels of total serum IgE (T-IgE) 9 and eosinophils 10 are linked to allergic illnesses, although the underlying patterns remain elusive. In this study, intrinsic features such as age, gender, sIgE, and T-IgE and clinical parameters such as the eosinophil percentage, eosinophil count, basophil percentage, and basophil count were compared between children with monosensitization and those with polysensitization.…”
Section: Introductionmentioning
confidence: 99%